Nanosponges As A Revolutionary Drug Delivery System For Skin Disorders: Advancements, Challenges, And Future Perspectives - N, Afreen N; Sharma, Aastha; Chauhan, Nidhi; Singh, Umakant; Sikarwar, Gaurav Singh; Madhuria, Neeraj (Journal of Neonatal Surgery, 2025)
Nanotechnology has significantly transformed drug delivery, particularly in dermatology, where conventional treatments often face limitations such as poor bioavailability, systemic side effects, and inconsistent drug release. Nanosponges (NS), with their porous, sponge-like structure, have emerged as a promising solution for targeted and controlled drug delivery in treating various skin disorders, including psoriasis, acne, eczema, and skin cancer. These nanoscale carriers enhance drug solubility, stability, and bioavailability while reducing toxicity and side effects. This review explores the recent advancements in nanosponge-based formulations, including β-cyclodextrin, ethyl cellulose, and polymeric nanosponges, and their potential applications in dermatology. Various preparation techniques, such as solvent-based synthesis, emulsion-solvent diffusion, and ultrasound-assisted synthesis, are discussed in detail. Characterization techniques include particle size analysis, zeta potential, drug loading capacity, and release kinetics. Despite their advantages, challenges such as large-scale manufacturing, regulatory concerns, and long-term biocompatibility must be addressed before clinical translation. Future research should optimise formulation stability, enhance specificity, and conduct rigorous in vivo studies to validate nanosponge efficacy. Integrating nanosponge technology with stimuli-responsive and intelligent delivery systems offers exciting prospects for personalized dermatological treatments. This paper comprehensively reviews nanosponge-based drug delivery systems for dermatological applications, emphasizing their potential to revolutionize topical and transdermal therapy. Addressing existing challenges will be crucial for their successful clinical implementation, ultimately improving patient outcomes and treatment efficacy in dermatology.